2005
DOI: 10.3402/tellusb.v57i2.16784
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Study of Tropospheric Aerosol and Radiation (ASTAR) 2000: Arctic haze case study

Abstract: A strong haze event occurred between 21 and 25 March in which the optical depth from ground-based observation was 0.18, which was significantly greater than the background value of 0.06. Airborne measurements on 23 March during this haze event showed a high aerosol layer with an extinction coefficient of 0.03 km −1 or more up to 3 km and a scattering coefficient from 0.02 in the same altitude range. From the chemical analyses of airborne measurements, sulfate, soot and sea salt particles were dominant, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Negative DRE values of similar or even stronger magnitude are also expected at least over the Arctic in January, because of the presence of Arctic haze (e.g. Hu et al, 2005;Yamanouchi et al, 2005) involving long-range transport of anthropogenic pollution from industrialized areas in Europe, North America and Asia. Such features do not appear in Figs.…”
Section: Shortwave Aerosol Direct Radiative Effect Computationsmentioning
confidence: 84%
“…Negative DRE values of similar or even stronger magnitude are also expected at least over the Arctic in January, because of the presence of Arctic haze (e.g. Hu et al, 2005;Yamanouchi et al, 2005) involving long-range transport of anthropogenic pollution from industrialized areas in Europe, North America and Asia. Such features do not appear in Figs.…”
Section: Shortwave Aerosol Direct Radiative Effect Computationsmentioning
confidence: 84%
“…O'Neill et al 2012documented an Arctic-wide dispersion of volcanic aerosols from the June 2009 Sarychev Peak eruptions. Subsequently, AOD increased regionally by as much as 0.05, an order of magnitude greater than normal for a quiescent stratosphere (Thomason et al, 2003;Yamanouchi et al, 2005).While it was once thought that minor volcanic eruptions had little and no lasting influence on high-latitude climate, the impact of more frequent and intense eruptions in recent years warrants investigation. The time series of BG AOD at Arctic sites can provide further insight.…”
Section: Daily and Long-term Variations In Aodmentioning
confidence: 99%
“…Monthly and year-to-year variations and trends in AOD and derived spectral parameters are presented. Corresponding, in situ measurements of equivalent black carbon (EBC) are similarly analyzed, updating the analysis of Sharma et al (2004;2013); and a compilation of BC data collected by aircraft (e.g., Schnell, 1984;Schnell et al, 1989;Skouratov, 1997;Yamanouchi et al, 2005;Brock et al, 2011;Warneke et al, 2010;Stone et al, 2010;Matsui et al 2011) are used to evaluate BC concentrations within the troposphere. The profiles are used to evaluate variations in atmospheric BC over time.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of absorbing particles in the troposphere causes a local warming at the altitude of their existence and, at the same time, a cooling below it at the ground. Measurements have shown that black carbon found in Arctic Haze events over Spitsbergen seem to be a minor but an important component, due to its absorbing properties [1]. In the frame of the iAREA Project (Impact of Absorbing aerosols on Radiative forcing in the European Arctic), a field campaign was performed from 26 March to 7 May 2015 at Ny-Ålesund.…”
Section: Introductionmentioning
confidence: 99%